Development and Method Validation for the Determination of Nitroimidazole Residues in Salmon, Tilapia and Shrimp Muscle. (27th November 2019) - Watson, Lynn; Potter, Ross; MacNeil, James D; Murphy, Cory
Abstract: The use of nitroimidazoles in aquacultured fish has been banned in many countries due to the suspected mutagenic and carcinogenic effects of these compounds. In response to the need to conduct residue testing of these compounds in fish, a simple, rapid, and sensitive method was developed and validated that is suitable for regulatory monitoring of nitroimidazole residues and their hydroxy metabolites in fish muscle tissue. Following solvent extraction of homogenized tissue and clean-up using a C18 SPE cartridge, analyses were conducted by ultra-performance UPLC-MS/MS. A precursor ion and two product ions were monitored for each of the parent compounds and metabolites included in the method. The validated method has an analytical range from 1 to 50 ng/g in the representative species (tilapia, salmon, and shrimp), with an LOD and LOQ ranging from 0.07 to 1.0 ng/g and 0.21 to 3.0 ng/g, respectively, depending on the analyte. Recoveries ranged from 81 to 124% and repeatability was between 4 and 17%. HorRat values were within typical limits of acceptability for a single laboratory. Working standards were stable for 12 months, extracts were stable for 5 days, andtissues for 2 months under appropriate storage conditions. This method was determined to be suitable for routine use for screening, quantification, and confirmation of nitroimidazole residues in a residue monitoring program for fish with regulatory oversight.